PENGARUH PENGENDALIAN INTERNAL, KOMITMEN ORGANISASI, ETIKA KERJA, DAN GENDER TERHADAP KINERJA KARYAWAN: STUDI KASUS PT GRAHA SARANA DUTA KANTOR PUSAT - Ramadani, Fitri Amalia; Dahlia, Lely (TRILOGI ACCOUNTING & BUSINESS RESEARCH, 2025)
This study aims to determine the effect of internal control, organizational commitment, work ethics, and gender on employee performance. The study was conducted at PT Graha Sarana Duta (PT. GSD) Head Office with a quantitative approach through a survey method. The respondents used in this study were permanent employees of PT. GSD Head Office with a sample size of 93 respondents. Data analysis was carried out descriptively to describe the characteristics of respondents and research variables, and testing was carried out using SEM PLS with SmartPLS software version 3. The results of the study showed that internal control, work ethics, and gender had a significant positive effect on employee performance, while organizational commitment did not affect employee performance. The results of this study provide practical contributions to management in designing performance improvement strategies that are more based on work systems and values and open opportunities for further exploration related to the role of gender in organizational structures and policies.Keywords: Gender; Internal Control; Organizational Commitment; Organizational Performance; Work Ethics